Understanding the Role of Canon Law in a Synodal Church: A Challenge and an Opportunity for Theologians - Turner, Emily P. (Theological studies, 2025)
For more than a century, canon law has been overwhelmingly understood as the purview of canonists, quite apart from the work of theologians. Insufficient understanding of and appreciation for the history and function of canon law on the part of theologians are both a product of this perceived separation and a factor contributing to its perpetuation. This article argues that the realization of the theological vision of Vatican II, and the success of the Synod on Synodality, will require greater understanding of the form and function of canon law in the Roman Catholic Church.